Scalable synthesis of strutted nitrogen doped hierarchical porous carbon nanosheets for supercapacitors with both high gravimetric and volumetric performances. (July 2021) - Chen, Chong; Zhao, Mingkun; Cai, Yuyan; Zhao, Guangzhen; Xie, Yong; Zhang, Li; Zhu, Guang; Pan, Likun
Abstract: Porous carbon nanosheets with high specific surface area have become the most promising electrode materials for supercapacitor, but their high pore volume leads to relatively low density and poor volumetric capacitance. In this work, strutted nitrogen doped hierarchical porous carbon nanosheets (SNPCNS), featuring three-dimensional nonaggregated architecture braced by struts have successfully been scalably synthesized via a novel calcium d -gluconate-exploding technique. The pyrolysis temperature and duration, and the mass ratio of calcium d -gluconate and urea formaldehyde resin are regulated for optimizing the specific surface area, pore volume and capacitive performance of SNPCNS. The optimized SNPCNS displays high specific surface area (539 m 2  g −1 ), rich surface heteroatoms (8.1 at.% for N) and high density (1.11 g cm −3 ). Therefore, the supercapacitor assembled by SNPCNS electrodes presents very high gravimetric/volumetric capacitances of 286 F g −1 /317 F cm −3 (in 6 M KOH) and 355 F g −1 /394 F cm −3 (in 1 M H2 SO4 ). Importantly, high gravimetric/volumetric energy densities of 40.5 W h kg −1 /44.9 W h L −1 (in ionic liquid) are achieved, which are superior to those of previously reported carbon nanosheets based symmetric supercapacitors. This work provides a new strategy for the mass and low-cost production of high-performance porous carbon nanosheets for energy storage. Graphical abstract: Image 1